Implementasi Nilai-Nilai Islam dalam Tradisi Poago di Desa Kapoa Barat Kabupaten Buton Selatan - Rifki Rifki; Madi Madi; Sulasri Sulasri (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to describe the implementation of the Poago tradition in Kapoa Barat Village, South Buton Regency, identify the Islamic values embedded within it, and explain its role as a form of local wisdom in the community. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving traditional leaders, religious leaders, village officials, tradition practitioners, and local community members. Data analysis was conducted through data reduction, data presentation, and conclusion verification. The findings reveal that the Poago tradition continues to be preserved as an integral part of the community’s cultural life and serves as a medium for strengthening social relationships among residents. The tradition embodies various Islamic values, including gratitude, mutual assistance, deliberation, social bonding, togetherness, and social care. These values reflect the harmonious integration of Islamic teachings and local cultural traditions. In addition to functioning as a means of cultural preservation, the Poago tradition contributes to strengthening social solidarity and serves as a medium for transmitting religious and moral values to younger generations. Therefore, the Poago tradition can be regarded as a form of local wisdom that remains relevant in maintaining social harmony and religious life within the community.